Comparative Cyto-morphometric Studies on Blood cells of Domestic Fowl, Guinea Fowl and Pigeon - Kumar, Naveen (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on blood cells of thirty healthy domestic fowl, guinea fowl and pigeon, ten birds of each group. Significantly higher length of erythrocytes as observed in guinea fowl followed by pigeon and domestic fowl. On the otherhand width of erythrocytes was higher in fowl then guinea fowl and lowest in pigeon, however differences being significant among all the three groups of birds. Diameter of heterophil was maximum in guinea fowl followed by domestic fowl and pigeon. With regard to diameter of eosinophil, the highest value was recorded in guinea fowl and pigeon then fowl. However, differences were significant among all three group of birds. The average diameter of basophils was higher in guinea fowl followed by pigeon and fowl. The diameter of lymphocytes was recorded higher in guinea fowl followed by pigeon and fowl. Further critical difference test revealed that significant difference was observed among domestic fowl and guinea fowl.